Arecoline increases basic fibroblast growth factor but reduces expression of IL‐1, IL‐6, G‐CSF and GM‐CSF in human umbilical vein endothelium. (19th December 2014) - Ullah, Mafaz; Cox, Stephen; Kelly, Elizabeth; Moore, Malcolm A. S.; Zoellner, Hans
<x xml:space="preserve">Abstract</x> Background Areca nut chewing is associated with oral submucous fibrosis (OSF). Raised vascular basic fibroblast growth factor may induce fibrosis. Arecoline is a muscarinic alkaloid in areca nut, which we earlier reported causes injury and necrosis of human endothelium. Materials and methods Human umbilical vein endothelial cells were exposed to arecoline with or without tumor necrosis factor‐α, and separately to acetylcholine, muscarine, or nicotine. Protein levels of basic fibroblast growth factor, as well as the inflammatory cytokines: granulocyte colony stimulating factor (G‐CSF), granulocyte‐macrophage colony stimulating factor, and Interleukins‐6, 1‐α and 1‐β, were determined by enzyme‐linked immunosorbent assay. mRNA levels were established by real‐time reverse transcription polymerase chain reaction. Results Basic fibroblast growth factor was released into the culture medium at arecoline levels causing necrosis (P < 0.05). This contrasted with an opposite effect of arecoline on levels of the inflammatory cytokines (P < 0.05). Tumor necrosis factor‐α increased IL‐6 and granulocyte‐macrophage colony stimulated factor, but arecoline reduced this stimulated expression (P < 0.05). Arecoline had no effect on mRNA for basic fibroblast growth factor, although there was reduced mRNA for the separate inflammatory cytokines studied. The effect of acetylcholine, muscarine, and nicotine was minimal and dissimilar to that of arecoline. Conclusions Data raise the possibility that arecoline‐induced, vascular basic fibroblast growth factor contributes to OSF, by combining increased growth factor expression with endothelial necrosis, and thus driving fibroblast proliferation.